Effect of Papaya Seed Freshing (Carica papaya) With Different Dosage As A Herbal Medicine Against The Parasite Argulus Indicus On Gold Cook Fish (Carassius auratus) - Sari, Erina Puspita; Budiyanto , Didik; Wirawan , Indra (Program Studi Budidaya Perairan Universitas Mataram, 2024)
Goldfish include ornamental fish with many fans because of various strains (Syaifudin., 2004). The type of parasite that often attacks freshwater fish is Trichodina sp. Dactylogyrus sp. Gyrodactylus sp. Ichtyopthirius Mulrifilis sp. Lernaea sp. Argulus sp. and Myxobolus sp (Zheila, 2013). Papaya seeds contain carpain alkaloids (Khrisna et al., 2008) which is also a vegetable insecticide (Kurnia et al., 2012). The data collection method used in this study is a complete random design (RAL) with 4 treatments as follows: A: Test media without papaya seed juice concentrate 0 ml/l of water, b test media with papaya seed juice concentrate 20 ml/l of water, C Test media with papaya seed juice concentrate 40 ml/l of water, d test media with papaya seed juice concentrates 60 ml/l of water. Requests D indicates the best dose among other treatments because carpain works to suppress the central nervous system (Nur, 2002) . Duke (1992) says, karpain has the activity of suppressing the central nervous system by binding to Na+ ions to the nerves. Na+ ions function to deliver nerve impulses until action occurs. The argulus nerve is associated with a sucker that functions to stick. The pressed nerve cannot deliver nerve impulses to the sucker resulting in argulus unable to infestation of mascoki fish. Giving papaya seed juice with different doses has a very significant effect on argulus parasites, 60 ml/l (treatment d) can suppress very high argulus namely 30.56%, a 40 ml/L donation (treatment C) can suppress argulus ie 25% of 20 ml/L (treatment B) can suppress argulus, which the same as 0%.